Hubungan Metode Pembelajaran Guru Dengan Konsentrasi Belajar Siswa Kelas 2 di SDN 10 Dungaliyo - Mukmin Kadoli Umar; Nur Indah DG. Mareto; Reynilda Reynilda; Nurlina A. Manrapi; Adelia Olii (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2026)
This study aims to identify the relationship between teachers’ teaching strategies and students’ learning focus in the second grade at SDN 10 Dungaliyo. A quantitative correlational approach was employed to examine the relationship between teacher teaching strategies (X) and student learning focus (Y). The population consisted of 18 second-grade students, with a sample of 6 students selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire and observations. Data analysis was conducted using the Pearson Product-Moment correlation test. The findings showed that teachers’ teaching strategies obtained an actual score of 268 out of 300 (89.3%), categorized as very high. Students’ learning focus achieved an actual score of 260 out of 300 (86.7%), also categorized as very high. The correlation analysis produced a coefficient of r = 0.71, indicating a strong positive relationship between teachers’ teaching strategies and students’ learning focus. These findings suggest that better teaching strategies contribute to higher student learning focus. Therefore, teachers should continue developing innovative and varied teaching strategies that match students’ characteristics to improve learning quality and sustain students’ concentration.